Análisis del significado de los verbos españoles venir y llegar, y sus equivalentes polacos - Tatoj, Cecylia (Neophilologica, 2012)
This article compares the meaning of the Spanish verbs venir and llegar, and their Polish counterparts in order to describe similarities and differences in the conceptualization of movement in both languages.